Influence of Eucalyptus globulus plantations on soil characteristics at different altitudinal levels - Carmen N. Vigo; Fely E. Oclocho-Garcia; Daniel Iliquín Trigoso; Manuel Oliva-Cruz (Trees, Forests and People, 2024)
This study evaluated the influence of Eucalyptus globulus L. plantations on the physical, chemical and biological properties of the soil in three districts: Magdalena, Tingo and San Isidro del Maino. The evaluation was carried out in six plots, three with eucalyptus and three with natural forests. In each plot with eucalyptus, 10 specimens were selected to measure their dasometric characteristics. Ten soil samples were taken at the base of each specimen to evaluate the bulk density and soil characterization, replicating the sampling in the natural forest plots. Additionally, biological sampling was carried out in each plot using the Rapid Soil Sampling Protocol, with a total of five quadrats per plot. The results showed significant differences in diameter at breast height (DBH), tree height and dry biomass among the districts evaluated. Trees in Magdalena presented the highest DBH and height, with an average biomass of 934.22 kg/tree, while those in Tingo showed the lowest values, with an average biomass of 230.00 kg/tree. Diverse flora species associated with both eucalyptus and natural forests were identified, reflecting a rich biodiversity in each district. Soils with eucalyptus in Tingo showed a predominantly clay texture, while in Magdalena and San Isidro del Maino a sandy loam texture predominated. In the natural forests, the soils in Tingo were also clayey, with more varied textures in the other districts. Bulk density was higher in forest soils in Tingo and in eucalyptus soils in San Isidro del Maino. Soils under eucalyptus had lower pH and lower electrical conductivity compared to natural forest soils. In terms of nutrients, the eucalyptus soils in Tingo and Magdalena showed higher phosphorus and potassium contents, while in San Isidro del Maino, the forest soils had higher levels. In general, eucalyptus soils showed higher levels of organic carbon, organic matter and nitrogen in Tingo and Magdalena, but lower in San Isidro del Maino. Biologically, natural forest soils exhibited a higher diversity and quantity of organisms compared to eucalyptus soils, especially in San Isidro del Maino. Detritivore indices were higher in natural forests, suggesting greater soil biodiversity. This higher diversity could be associated with better soil quality in these systems, highlighting the importance of natural forests in maintaining healthy soils.